Configuring Microsoft Outlook 2003 (Elsevier Digital Press, 2005)
One of the challenges of administering and supporting Microsoftreg; Outlook 2003 is that it stores settings in so many different places - in the Windows registry, as files in the users profile folders, and in the information store itself. Configuring Microsoftreg; Outlook 2003 pulls together in one volume the information that administrators in organizations of all sizes need to understand, deploy, and manage settings for Microsoft Outlook 2003. It covers configuration issues for environments where Microsoft Exchange is the mail server and also for those using IMAP4 or POP3. The book gives special attention to security issues, including recommended configuration of Outlooks built-in security features and methods for locking down Outlook with Group Policy Objects and other techniques. Readers will learn how to: * Configure the new Cached Exchange mode and RPC over HTTP connections in Outlook 2003 * Discover undocumented settings for Microsoft Exchange Server and use them to deploy or modify Outlook mail profiles * Migrate both user data and settings to a new machine * Use tools such as MFCMAPI and Outlook Spy to explore Outlook's data and settings * Configure an archive .pst file in the new Unicode format that supports up to 20GB of data * Use scripts to handle challenging configuration tasks such as granting Reviewer access to a Calendar folder, or adding a second Exchange mailbox to an Outlook profile.